Development of Canva-Based Photo Story Media in Indonesian Language Learning for Fifth Grade Students at Islamic Elementary Schools: Pengembangan Media Photo Story Berbasis Canva Pada Pembelajaran Bahasa Indonesia Siswa Kelas V Di Sekolah Dasar Islam - Dani, Andi Rizki; Munirah, Munirah; Rimang, Siti Suwadah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Indonesian language learning in elementary education emphasizes literacy skills, yet students’ reading interest and comprehension remain limited due to unengaging instructional media. Specific Background Classroom practices are dominated by textbooks with minimal interactive support, while students show higher interest in visual and narrative-based materials. Knowledge Gap Previous studies highlight visual media benefits, but there is limited development of Canva-based photo story media specifically designed to optimize learning outcomes in short story materials. Aims This study aims to develop and analyze the validity, practicality, and effectiveness of Canva-based photo story media for fifth-grade Indonesian language learning. Results Using a Research and Development approach with the Four-D model, the media achieved high validity (media 92.64% and material 94.23%), strong practicality based on teacher (95.45%) and student responses (86.05%), and improved learning outcomes from a mean score of 58.31 to 85.52. Novelty The innovation lies in integrating visual design, narrative structure, and digital accessibility aligned with elementary student characteristics to create contextual and interactive learning experiences. Implications The findings indicate that Canva-based photo story media provides a feasible digital learning alternative that supports student engagement, comprehension, and improved academic performance in Indonesian language learning. Highlights• High validity confirmed by expert evaluation across media and material dimensions• Strong usability indicated by positive teacher and student responses• Significant improvement observed between pretest and posttest performance KeywordsPhoto Story; Canva; Learning Outcomes; Digital Media; Indonesian Language